Evaluation of safflower (Carthamus tinctorius L) genotypes against salinity stress: Evaluation of safflower (Carthamus tinctorius L) genotypes against salinity stress - A AZIZ QURESHI,; P KADIRVEL,; N MUKTA,; CH V HARIPRIYA, (Journal of Oilseeds Research, 2020)
Safflower genotypes were evaluated for salinity stress using irrigation water with 5 EC levels through paper towel method. Among the 24 genotypes tried, performance of 5 genotypes was prominent in terms of shoot length and weight at 15 days growth. The genotype IC-406052 showed 23% reduction and genotype SSF-733 showed 65% reduction with EC of 10 dS/m against zero salinity. Highest reduction of shoot weight was noticed in SSF-733(54%) and minimum was recorded in IC-406052 (26%) with EC of 10 dS/m compared to zero salinity.